A retrospective evaluation of the relationship between symmetric dimethylarginine, creatinine and body weight in hyperthyroid cats - Szlosek, Donald (PLoS One, 2020)
Hyperthyroidism in cats can mask changes in renal function, including chronic kidney disease (CKD), because of hyperfiltration and muscle loss. Symmetric dimethylarginine (SDMA) has been shown to increase earlier than creatinine in cats with renal dysfunction, and, unlike creatinine, SDMA is not impacted by lean muscle mass. The aim of this study was to describe the relationship between SDMA, creatinine, body weight and TT4 over time during treatment of hyperthyroidism. Cats were retrospectively identified from the US IDEXX Reference Laboratories database where TT4, SDMA and creatinine were measured on the same cat at multiple time points. A hyperthyroid treated group was identified (TT4 ≤ 4.7 μg/dL and decreased by a minimum of 2.5 μg/dL) that had body weight and laboratory results available from more than one visit, and was used to evaluate body weight, creatinine, SDMA and TT4 pre-treatment and at 1–30, 31–60, 61–90, 91–120 days post-treatment. Creatinine significantly decreased with increasing concentrations of TT4 (Spearman’s ρ = -0.37, P < 0.001), whereas SDMA did not. Body weight, SDMA and creatinine concentrations significantly increased during the immediate 1–30 day post-treatment period (P < 0.012, P < 0.001, P < 0.001, respectively). During treatment creatinine continued to increase as cats gained weight. In contrast, SDMA remained stable during treatment and was comparable to age-matched control cats. Therefore, SDMA may be a more reliable biomarker of renal function than creatinine in hyperthyroid cats before and during treatment.